Travel Time and Attrition From VHA Care Among Women Veterans: How Far is Too Far?. Issue 4 (April 2015) - Friedman, Sarah A.; Frayne, Susan M.; Berg, Eric; Hamilton, Alison B.; Washington, Donna L.; Saechao, Fay; Maisel, Natalya C.; Lin, Julia Y.; Hoggatt, Katherine J.; Phibbs, Ciaran S.
Abstract : Background: Travel time, an access barrier, may contribute to attrition of women veterans from Veterans Health Administration (VHA) care. Objective: We examined whether travel time influences attrition: (a) among women veterans overall, (b) among new versus established patients, and (c) among rural versus urban patients. Research Design: This retrospective cohort study used logistic regression to estimate the association between drive time and attrition, overall and for new/established and rural/urban patients. Subjects: In total, 266, 301 women veteran VHA outpatients in the Fiscal year 2009. Measures: An "attriter" did not return for VHA care during the second through third years after her first 2009 visit ( T 0 ). Drive time (log minutes) was between the patient's residence and her regular source of VHA care. "New" patients had no VHA visits within 3 years before T 0 . Models included age, service-connected disability, health status, and utilization as covariates. Results: Overall, longer drive times were associated with higher odds of attrition: drive time adjusted odds ratio=1.11 (99% confidence interval, 1.09–1.14). The relationship between drive time and attrition was stronger among new patients but was not modified by rurality. Conclusions: Attrition among women veterans is sensitive to longer drive time. Linking new patients to VHA services designed to reduce distance barriers (telemedicine, community-based clinics, mobile clinics) may reduce attrition among women new to VHA.